The future is female : gynoidian skins and prosthetic experience : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Media Studies at Massey University, Wellington, New Zealand - Dillon, Sarah M (Massey University, 2017)
The female cyborg, or ‘gynoid’, has historically recurred in cinema as a trope by which the female form magnetises anxieties about new experiences proffered by digital technologies. This thesis draws on phenomenological theory, including Laura Marks’ notion of the ‘haptic’ and Jennifer Barker’s method of 'textural analysis’, to conceptualise the affective experiences that gynoids within a strand of contemporary Hollywood films promote. The gynoidian protagonists of Spike Jonze’s Her (2013), Alex Garland’s Ex Machina (2015), and Luc Besson’s Lucy (2014) attempt to engage the viewer in various ‘prosthetic’ (Alison Landsberg) encounters: tactility, sensations, gaming and sexual experiences. I argue that these films use sophisticated stylistic means, including what I term ‘haptic absence’, to employ the gynoid’s body or voice as a conduit in promoting a more positive or celebratory exploration of the affects produced by new technologies. The films demonstrate that within this particular cultural milieu, phenomenological experiences of cinema have the potential to open up a less fraught relationship between women and technology.
Keywords: Cyborgs in motion pictures; Women in motion pictures; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Film